BINOL Macrocycle Derivatives: Synthesis of New Dinaphthyl Sulfide Aza Oxa Thia Crowns (Lariats) - Abbas Shockravi; Shahram Mehdipour-Ataei; Esmael Rostami (Journal of Chemistry)
In this research work, dinaphthyl sulfide diester was prepared from the reaction of 1,1′-thiobis (2-hydroxy naphthalene) and methylchloroacetate. Its aza-macrocyclic derivative was synthesized from the reaction of dinaphthyl sulfide diester and diethylenetriamine. Lariats were prepared from the reaction of chloroamides (four derivatives) and initial macrocycle. Chloroamides were synthesized from the reaction of amines (aniline, benzylamine, 8-amino quinoline and 4-amino azobenzene) and chloroacetyl chloride. All the materials were identified by IR, 1H NMR, 13C NMR, and mass spectroscopies, and elemental analysis.